Efficacy and Safety of Orogastric vs. Nasogastric Tube Feeding in Preterm Infants: A Systematic Review and Meta-Analysis - Huazi Liu; Qiang Fei; Tianming Yuan (MDPI AG, 2024)
Background: Enteral nutrition can be delivered to the stomach using nasogastric or orogastric tubes, with each route having advantages and disadvantages. This meta-analysis aimed to compare the effects of these methods on growth, development, and the incidence of adverse outcomes. Methods: This analysis included studies that enrolled preterm infants who received nasogastric or orogastric tube feeding. We searched databases including PubMed, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials. Only randomized controlled trials were selected. We used version 2 of the Cochrane tool to assess the risk of bias in randomized trials and Review Manager 5.4 software to perform the meta-analysis. Results: Six studies involving 265 preterm infants were included. The meta-analysis showed that orogastric tube feeding took significantly longer to establish full enteral tube feeding compared to nasogastric tube feeding (MD = 1.62, 95% confidence interval [CI]: 0.99-2.26, Z = 5.02, p < 0.01). However, no significant difference was observed between the two groups regarding time to regain birth weight (MD = −0.38, 95% CI: −2.2-1.44, Z = 5.02, p = 0.68). Data on adverse events were insufficient to perform a combined analysis. Conclusions: Preterm infants fed via nasogastric tubes took less time to reach full enteral feeding than those fed via orogastric tubes. Further research is required to evaluate the effect of feeding routes on adverse outcomes.